Current Evidence on Atypical Odontalgia: Diagnosis and Clinical Management - Yoshihiro Abiko; Hirofumi Matsuoka; Itsuo Chiba; Akira Toyofuku (Hindawi Limited, 2012)
Patients with atypical odontalgia (AO) complain of medically unexplained toothache. No evidence-based diagnostic criteria or treatment guidelines are yet available. The present paper addresses seven clinical questions about AO based on current knowledge in the literature and discusses diagnostic criteria and guidelines for treatment and management. The questions are (i) What is the prevalence of AO in the community? (ii) What psychological problems are experienced by patients with AO? (iii) Are there any comorbidities of AO? (iv) Is local anesthesia effective for the relief of pain in AO? (v) Are there any characteristic symptoms of AO other than spontaneous pain? (vi) Are antidepressants effective for treatment of AO? (vii) Are anticonvulsants effective for treatment of AO? Our literature search provided answers for these questions; however, there is insufficient evidence-based data to establish guidelines for the diagnosis and treatment of AO. Overall, some diagnostic criteria for neuropathic pain and persistent dentoalveolar pain disorder may be applied to AO patients. The patient's psychogenic background should always be considered in the treatment and/or management of AO. The clinicians may need to treat AO patients using Patient-Oriented Evidence that Matters approach.